FINANCIAL BEHAVIOR ANALYSIS OF COCONUT FARMERS IN BIREUEN REGENCY - Baihaqi, Akhmad; Ramadhani, Muhammad; Bagio, Bagio; Marsudi, Edy (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
Bireuen Regency is one of the areas in Aceh Province which has a superior commodity to be cultivated compared to other commodities such as coconut. The existence of consumptive behavior of coconut farmers is caused by a person's lack of understanding of how to manage finances in a good and right way. For this reason, a deep understanding of farmer behavior in managing their finances, as well as their interest in being involved in formal financial institutions. The purpose of this study was to determine education, financial knowledge, income, financial attitudes and use of financial institutions influence the financial management behavior of coconut farmers in Bireuen District. The sampling method used the slovin method and the sample for this study was 100 coconut farmers in South Peusangan District, Juli and Jeumpa determined the research area by purposive sampling. The analytical method used is ordinal logistic regression analysis with the help of SPSS 22.0 software. The results of the study concluded that the financial behavior of coconut farmers which showed the variables of education, financial knowledge, income, financial attitudes and use of financial institutions had a significance <0.05 on the management behavior of coconut farmers in Bireuen Regency. In the education variable of coconut farmers belonging to the high school (SMA) level of education, the financial knowledge variable explains that coconut farmers have fairly good financial knowledge,